Teachers’ voices of TPACK practices on ELT in the post-COVID-19 pandemic - Dewi Rochsantiningsih; Lailatun Nurul Aniq (UPT Bahasa Universitas Tanjungpura, 2023)
This narrative study aimed to interpret evolving themes of teachers' TPACK practices through an entirely different lens. This study engaged two in-service EFL teachers, one who taught in a rural school and another who taught in an urban school. This study was conducted from May to October. In-depth interviews were utilised to shed light on their emotional experiences. Then, we analysed the data through Critical Thematic Analysis. Findings demonstrated how ongoing regulations generated conditions teachers encountered with shifting teachers’ paradigms. Participants truly believed that their TPACK has transitioned to the enhancement of the dominant technology-related knowledge domain (TCK, TPK & TPACK). However, they experienced a deterioration of the quality of the non-technology-related knowledge domain (CK, PK & PCK). There was a gap between teachers' perceived importance of technology-integrated activities and actual integration, which remained a persistent barrier to teachers' technology integration. The study suggests policymakers should pay heed to maintaining sustainable educational system stability rather than forcing teachers to implement an unsteady policy.